Business Model Adaptation For Foreign Company To Navigate Local Content Requirements In Indonesia’s Upstream Oil and Gas Industry In 2034 Using Inductive Scenario Planning Approach (Case Study Tas) - Ratih Dwi Mutia; Yos Sunitiyoso; Ahmad Yuniarto (Publikasi Indonesia, 2025)
Complying with local content regulations in the upstream oil and gas industry presents a significant challenge. These regulations aim to enhance local capability, and the industry's yearly transaction value greatly impacts the local industry, necessitating the use of local products. However, despite requiring high technology, this industry mostly relies on imported products. To address this challenge, our research employs a systematic approach that combines scenario planning with Analytic Hierarchy Process (AHP) analysis. Our primary goal is to develop a comprehensive framework that empowers organizations to optimize their business strategies within the context of localization projects. By integrating scenario planning, which allows for the exploration of diverse future scenarios, with AHP analysis, which offers a structured analytical foundation for evaluating and selecting strategies, our research equips decision-makers with a powerful toolset. Through extensive case studies and meticulous analysis, our research sheds light on the nuanced decision-making processes and strategic adaptations that can be achieved through the synergy of scenario planning and AHP analysis in the domain of localization projects. Our findings and insights provide practical guidance to decision-makers grappling with the complexities of local content compliance and the long-term sustainability of business strategies.